Analysis of Brilink Arif Cell Agent Service towards Customer Satisfaction - Awandah, Nur; B, Sofyan; Yaqub, Rahman (Journal of Management and Administration Provision, 2024)
Customer Satisfaction of BRILink Arif Cell Agents, Rappang Branch. By using a survey method with a questionnaire distributed to customers who use the BRILink Arif Cell service. The population in this study were customers of BRILink Arif Cell Agents, Rappang Branch, carried out using the Accidental Sampling technique using the Slovin formula, so that 63 consumers were obtained as respondents. The research method uses quantitative research. The data used are primary data obtained using questionnaires, observations, interviews, and documentation. The data analysis technique used is validity and reliability test analysis, using the IBM SPSS statistical application 26.6.